Analisis Kecenderungan Gangguan Kepribadian Ambang (BPD) pada Tokoh Utama Novel Jugigo Sipeun Ai Karya Lee Kkoch-Nim - Amala, Az Zahra Ahsana; Rosyadi, Alfiana Amrin (Universitas Gadjah Mada, 2025)
This study analyzes the tendency toward borderline personality disorder (BPD) in Ji Ju-yeon, the main character in Lee Kkoch-Nim's novel Jugigo Sipeun Ai (죽이고 싶은 아이) (2021). The research employs a qualitative approach with descriptive analysis and applies the theory of abnormal psychology developed by Durand, Barlow, and Hofmann as outlined in Essentials of Abnormal Psychology (2019). The study aims to describe the symptoms of BPD shown by the character and identify the underlying causes of her psychological condition. The findings reveal that Ji Ju-yeon exhibits several prominent symptoms of borderline personality disorder, including: (a) strong obsession to avoid abandonment, (b) intense but unstable relationships, (c) unstable self-image, and (d) emotional instability shown by self-harm and intense anger, or difficulty controlling anger. The analysis also identifies key contributing factors to the development of these tendencies. The contributing factor here is dysfunctional parenting that leads to emotional neglect and a lack of emotional validation. This study emphasizes that the portrayal of abnormal psychological traits in literary characters can reflect complex mental health issues rooted in interpersonal and environmental factors. It also highlights how literature can serve as a medium for exploring and understanding psychological disorders more deeply.